Cultural Capital and Community in Contemporary City-wide Reading Programs - Rehberg Sedo, DeNel (Mémoires du livre / Studies in Book Culture, 2010)
There are currently more than 500 city-wide reading projects in the US, and dozens in Canada and the UK. Through creative and traditional programming, such as canoe treks and book discussion groups, producers often use the One Book, One City model to “create community” through a selected text. This essay argues that instances of coming together to share reading experiences can be considered literary cultural fields as the French sociologist Pierre Bourdieu conceived them. Readers seek cultural capital by participating in events because participation in book culture is considered a commendable and valuable activity. However, in order to participate, one needs to already have a certain amount of cultural literacy and capital. The essay offers an analysis of readers’ articulations of why they do and do not participate in city-wide book programming to help us better understand the motivations, pleasures and obstacles of membership in ephemeral reading communities.